FINANCIAL AND COST MANAGEMENT STRATEGIES FOR HOTEL OPERATIONS WITH PUBLIC SECTOR ACCOUNTING (CASE STUDY OF EHNAII HOTEL BANDUNG) - Afianti, Azzachra Fitri; Megasari, Cesaria (Akademi Komunitas MAPINDO, 2022)
A hotel is a building or part of a building dedicated to providing accommodation and food for everyone, as well as access to other services and facilities. The system in national financial management is based on the process and model of public sector accounting which as a scientific field that is receiving special attention from the current government, is evidenced by the many changes and improvements to the management system including management accounting. Public sector accounting plays an important role in the smooth functioning of the organization which has been managed by government agencies, especially in terms of the effectiveness of revenue and expenditure management in order to achieve the expected goals. The implementation of public sector accounting is going well, so the management of EnHaii Hotel must have a good plan and strategy in accordance with applicable regulations and established procedures. Operational costs submitted to budget users must be well planned according to established rules and on time. Keywords: Reveneu Management, Management, Public Sector Accounting